Age at natural menopause and risk of diabetes in adult women: Findings from the China Kadoorie Biobank study in the Zhejiang area. Issue 4 (5th December 2017) - Wang, Meng; Hu, Ru‐Ying; Wang, Hao; Gong, Wei‐Wei; Wang, Chun‐Mei; Xie, Kai‐Xu; Chen, Zheng‐Ming; Guo, Yu; Yu, Min; Li, Li‐Ming
Abstract : There has been considerable professional debate on the association between age at menopause and diabetes risk, while the findings are controversial. This study explored the association between late menopause and the prevalence of diabetes in the Chinese population. With data from part of the baseline survey of China Kadoorie Biobank from Zhejiang Province, our study found that women with menopause at a later age (≥53 years) were 1.21 (95% CI: 1.03–1.43) times more likely to have diabetes in comparison with those with menopause at 46–52 years. Abstract: Aims/Introduction: There has been considerable professional debate on the association between age at menopause and diabetes risk, while the findings are controversial. The present study explored the association between late menopause and the prevalence of diabetes in the Chinese population. Material and Methods: The data were part of the baseline survey of China Kadoorie Biobank from Zhejiang Province. A total of 17, 076 postmenopausal women were included in the present study. Logistic regression models were used to calculate the adjusted odds ratios and their 95% confidence intervals. Results: Of the participating women, 1, 288 (7.54%) had type 2 diabetes. In comparison with those with menopause at 46–52 years, women with menopause at a later age (≥53 years) were 1.21‐fold (95% confidence interval 1.03–1.43) more likely to have diabetes. Conclusions: The present findings suggested that later age at menopause was associated with an increased prevalence of diabetes.